Evaluation of cognitive assessment and cognitive intervention for people with multiple sclerosis. Issue 1 (1st January 2002) - Lincoln, N B; Dent, A; Harding, J; Weyman, N; Nicholl, C; Blumhardt, L D; Playford, E D
Abstract : Objectives: Cognitive problems in multiple sclerosis are common but any possible benefits of treatment remain uncertain. The aim of the study was to evaluate the benefits of providing a psychology service, including cognitive assessment and intervention, to patients with multiple sclerosis. Method: The study was a single blind randomised controlled trial. A total of 240 patients with clinically definite, laboratory supported, or clinically probable multiple sclerosis were recruited from an multiple sclerosis management clinic and assessed on a brief screening battery. They were randomised into three groups. The control group received no further intervention. The assessment group received a detailed cognitive assessment, the result of which was fed back to staff involved in the patients' care. The treatment group received the same detailed cognitive assessment and a treatment programme designed to help reduce the impact of their cognitive problems. Patients were followed up 4 and 8 months later on the general health questionnaire (GHQ-28), extended activities of daily living scale, SF-36, everyday memory questionnaire, dysexecutive syndrome questionnaire, and memory aids questionnaire. Results: The three groups were compared on the outcome measures at 4 and 8 months after recruitment. There were few significant differences between the groups and those that occurred favoured the control group. Overall, the results showed no effect of the interventions on mood, quality of life, subjective cognitive impairment or independence. Conclusions: The study failed to detect any significant effects of cognitive assessment or cognitive intervention in this cohort of people with multiple sclerosis.